Training in the Great Recession: Evidence from an individual perspective - Daniel Dietz; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
This paper analyses the effect of the economic crisis in 2008 and 2009 on individual training activities of different employee groups within establishments. We use a unique German linked employer-employee panel data set with detailed information on individual training history (WeLL-ADIAB). The so-called Great Recession can be seen as an exogenous, unexpected, and time-limited shock. Therefore, our quasi-experimental setting using Diff-in-Diff analyses reveals the causal impact of the crisis on the training participation and the number of training measures. We find a direct negative effect of the crisis on individual training activities in 2009 and 2010. The negative effect therefore sets in with a time lag and lasts until after the recession. Furthermore, the recession effect is stronger for employees in unskilled jobs than for employees in skilled jobs.
Keywords: M53; O16; 330; Training; Financial Crisis; Linked Employer Employee Data Set